Added dietary fat improves growth performance and feed efficiency in growing-finishing pigs under commercial conditions - Drtiz, S.S.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of480 pigs was used in an experiment conducted in a commercial research facility to determine the influence of fat additions to the growing-finishing diet on pig performance and carcass composition. Adding fat to the diet from 80 to 265 lb increased ADG and FIG by 1 and 2%, respectively, for each 1%added fat. The growth response was greatest during the initial phase of the trial (80 to 130 lb) and declined as the trial progressed. The feed efficiency response was consistent throughout the trial. After adjusting for the greater carcass weight of pigs consuming the high fat diets, carcass parameters were not influenced by fat addition to the diet.
Keywords: Swine; Dietary fat; Growing-finishing pig; Growth